Do Income Disparities dissipate across the US States? Experimenting with a Vector Error Correction Model - Stilianos Alexiadis; Konstantinos Eleftheriou; Peter Nijkamp (Tinbergen Institute, 2013)
This paper examines the long-run trends in per-capita income across the US states (1929-2005). Our analysis advocates and implements a Vector Error Correction Model (VECM), in order to investigate whether disparities in per-capita income embody a stable long-run relation. The empirical application is supplemented with Factor Analysis to identify groups of States with a common behaviour in terms of per-capita income.
Keywords: C22; R10; 330; Intraregional income disparities; Vector Error Correction Model; Factor Analysis